Case Report: Angioimmunoblastic T-cell lymphoma with coexisting plasma cell tumors: three cases and review of the literature - Yang, Yulin; Bao, Xingshuo; Huang, Wei (Frontiers in Oncology, 2025)
Angioimmunoblastic T cell lymphoma (AITL) is classified as a nodal T-cell lymphoma from T follicular helper(Tfh) cells. Dysfunctional Tfh cells can lead to abnormal B cell regulation and plasma cell differentiation in AITL. However, the coexistence of AITL with plasma cell tumors is exceedingly rare. Here, we report three patients diagnosed with AITL accompanied by monoclonal gammopathy of undetermined significance (MGUS), smoldering multiple myeloma (SMM), and multiple myeloma (MM). The clinicopathologic findings, together with a review of previously reported cases, provide insight into the possible biological relationship between AITL and plasma-cell neoplasms. Epstein–Barr virus (EBV) infection was detected in all cases, suggesting a potential—though unproven—association between EBV-driven immune dysregulation and plasma-cell proliferation. Case analysis showed that some monoclonal plasma cells originated from the interior of AITL, while others originated from the bone marrow. This indicated that the evolution of plasma cell tumors may arise from either the lymphoma microenvironment or the systemic immune status. In cases of coexistence of AITL and plasma cell tumors, the treatment containing anti-MM drugs such as lenalidomide was usually recommended and might bring therapeutic benefits. Careful identification of monoclonal plasma-cell populations is therefore important for accurate diagnosis and individualized management of AITL.